Pengaruh Quantum Teaching Terhadap Minat Belajar Aqidah Akhlak Peserta Didik Mts Pondok Pesantren Ddi Manahilil UlumKaballangan Kabupaten Pinrang - Ibrahim Ibrahim (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2018)
This article aims to determine the intensity of the implementation of quantum teaching, the interest in learning Aqidah Akhlak. This type of research is field research and includes quantitative research. Data obtained through observation, questionnaires and documentation. Data were analyzed descriptively and inferentially, using statistical processing software. The results of this study were, (1) The intensity of the implementation of Quantum teaching, was in the low category. (2) The interest in learning Aqidah Akhlak learners (variable Y) is in the high category. (3) The results of the hypothesis test concluded that there is an effect of quantum teaching on the learning interests of Aqidah Akhlak MTs students in DDI Manahilil Ulum Kaballangan Islamic Boarding School Pinrang Regency. The implications of this study are, it is expected that educators, to always strive to be professional educators by attending seminars, training, workshops, comparative studies to institutions that are central to learning Quantum Teaching.